Разработка технологии хлебных изделий обогащенных йодосодержащими препаратами - Соловьёва, Е. А.; Батракова, Татьяна; Губеня, Алексей Александрович (My University, 2013)
The change of the human diet increases the role of bread. The bakery products creation for special purposes, which have therapeutic or prophylactic properties, thanks to the addition of iodine drugs to the formulation is promising. Materials and methods. The criteria for the enrichment of bread are selected on the basis of biomedical, technological and economic aspects. Determination of iodine was performed by standard methods. Result. The expediency of making dietary supplements Fitoyod of 0.0001 kg per 100 kg of flour for making bread from wheat flour, regardless of the method of preparation and formulation of the test. Scientifically justified use of dietary supplements, Fitoyod for the enrichment of bread intended for the prevention of diseases related to iodine deficiency. The chemical composition and technological properties of dietary supplements Fitoyod, allowing research to substantiate the possibility of its use and administration in the production of bread. The effect of dietary supplements Fitoyod on the process of maturation of the test and the quality of finished products depending on various technological factors: dosage of dietary supplements Fitoyod composition formula and method of preparation of the test. Conclusion. The research resulted in the practical application of scientifically proven dietary supplement Fitoyod to create a new kind of bakery products enriched with physiologically functional food ingredients in, intended for the prevention of diseases related to iodine deficiency in the Republic of Bashkortostan. Изменение рациона человека повышает роль хлеба. Перспективным является создание хлебных изделий специального назначения, которые имеют лечебные или профилактически свойства, благодаря введению в рецептуру йодсодержащих препаратов. Материалы и методы. Критерии обогащения хлеба выбраны на основании медико-биологических, технологических и экономических аспектов. Определение содержания йода проводили стандартными методами. Результаты. Целесообразно вносить БАД «Фитойод» в количестве 0,0001 кг на 100 кг муки при приготовлении хлеба из пшеничной муки. Научно обосновано применение БАД «Фитойод» для обогащения хлеба предназначенного для профилактики заболеваний связанных с йододефицитом. Исследован химический состав, технологические свойства БАД «Фитойод», позволяющие научно обосновать дозы ее использования при производстве хлеба. Выявлено влияние БАД «Фитойод» на процессы созревания теста и качество готовых изделий в зависимости от различных технологических факторов: дозировки БАД «Фитойод», состава рецептуры и способа приготовления теста. Научно обосновано применение БАД «Фитойод» для нового вида хлебного изделия, обогащенного физиологически функциональными пищевыми ингредиентами, предназначенного для профилактики заболеваний связанных с йододефицитом. Результаты являются особо актуальными для организации промышленного производства хлеба в Республике Башкортостан.
Будь ласка,підкажіть, якщо невірно зроблена цитата. Цитату потрібно однією мовою чи трьома? Згідно прикладу потрібно однією мовою, а в зауваженні - трьома. Дякую!
Keywords: iodine; bread; йод; хлеб; кафедра машин і апаратів харчових та фармацевтичних виробництв